Hubungan Minat Belajar dan Hasil Belajar Fisika Kelas XI MIPA SMAN 1 Bungo - Mahdiyyah Daeng Hanafi; Meri Gusrita; Aminatussaadah Aminatussaadah; Tinur Hasibuan; Sakahuni Sakahuni (Universitas PGRI Semarang, 2021)
This study aims to determine the relationship between interest in learning and learning outcomes of physics class XI MIPA students at SMAN 1 Bungo. This type of research is descriptive quantitative research. Data collection techniques in this study used a questionnaire instrument and test questions. To measure interest in learning using an interest scale test which is based on content validation. The learning outcome test uses multiple choice questions with a total of 25 items with the material elasticity and hooke's law. Respondents in this study were students of class XI MIPA 4, XI MIPA 5, XI MIPA 6 at SMAN 1 Bungo. The sampling technique uses random sampling technique. The method used in this research is Descriptive Statistics. The data analysis test used was the Normality Test, Homogeneity Test and Correlation Test. Based on the results of this study indicate that interest in learning has a positive and significant relationship to the learning outcomes of students in class XI MIPA 4, XI MIPA 5, and XI MIPA 6.